2021
DOI: 10.3389/fsoc.2021.605865
|View full text |Cite
|
Sign up to set email alerts
|

Self-Harm Among School-Going Adolescent Survivors of Sexual Violence Victimisation: A Cross-Sectional Study

Abstract: Background: A growing body of evidence from high-income contexts suggests a strong association between sexual violence victimisation and self-harm and eventual suicide. However, both sexual violence and self-harm among adolescents are still less researched in sub-Saharan African countries, including Ghana.Objectives: To estimate the 12-month prevalence of self-harm, and to describe the associated factors and reported reasons for self-harm among school-going adolescent survivors of sexual violence victimisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
(117 reference statements)
1
2
0
Order By: Relevance
“…Our results are supported by evidence that sexual violence victimization is associated with high rates of self-harm thoughts and behaviors [ 39 , 40 ]. This shows the profound impact that experiences with sexual violence can have on the mental health of adolescent girls in the DR. Our study also found that the most common perpetrators of sexual violence were current or former romantic partners, indicating that adolescent dating violence (ADV) may have a significant impact on the mental health of adolescent females, which aligns with studies signaling adolescent women as the most vulnerable group for IPV [ 26 ].…”
Section: Discussionsupporting
confidence: 83%
“…Our results are supported by evidence that sexual violence victimization is associated with high rates of self-harm thoughts and behaviors [ 39 , 40 ]. This shows the profound impact that experiences with sexual violence can have on the mental health of adolescent girls in the DR. Our study also found that the most common perpetrators of sexual violence were current or former romantic partners, indicating that adolescent dating violence (ADV) may have a significant impact on the mental health of adolescent females, which aligns with studies signaling adolescent women as the most vulnerable group for IPV [ 26 ].…”
Section: Discussionsupporting
confidence: 83%
“…This proportion is significantly higher than the 51% of 14-to 18-year-olds recruited through schools who reported engaging in intentional NSSI in the past year (Ammerman & Brown, 2018) or the 30% of a South Korean community sample who reported engaging in self-injurious behavior (Son et al, 2021). It was also significantly higher than the 38.7% reported self-harm among 297 adolescents who had experienced sexual violence victimization out of 1,723 surveyed in the WHO-Global School-based Student Health Survey in Ghana (Quarshie, 2021). Because the participants in this study were adolescents referred for treatment after experiencing sexual abuse, it may be appropriate to compare them to a clinical population.…”
Section: Discussionmentioning
confidence: 83%
“…Negative experiences such as trauma and childhood maltreatment are considered common socioenvironmental predictors of all types of self-harm (Nock, 2010; Serafini et al, 2017). Sexual abuse, in particular, is one of the strongest risk factors for both suicidal and nonsuicidal self-harm in adolescence (El Nagar et al, 2022; Quarshie, 2021; Soylu & Alpaslan, 2013). One study reported that more than 60% of people who experienced sexual abuse in childhood have had suicidal ideation, and 24.5% have attempted suicide (Soylu & Alpaslan, 2013).…”
Section: Self-harm In Sexually Abused Adolescentsmentioning
confidence: 99%